The role of libraries in curriculum implementation at SMP Kartika XIX-2 - Farhan Noorfansyah Sucahyo; Angga Hadiapurwa (Himpunan Pengembang Kurikulum Indonesia, 2025)
This article aims to examine the strategic role of school libraries in supporting the implementation of the Kurikulum Merdeka at the Junior High School (Sekolah Menengah Pertama or SMP) level. This research was conducted through direct interviews with library managers and observations of the available supporting facilities and resources. The primary focus of this study is on how the library provides effective and relevant teaching materials, coordinates with teachers to support teaching and learning activities, and carries out various innovations to adapt to the demands of the more flexible and student-centered Merdeka Curriculum. The library functions not only as a reading space but also as a learning resource center that supports the development of students’ literacy and independent learning. The findings of this research are expected to provide a comprehensive overview of the school library’s contribution to creating a learning environment that is adaptive and responsive to curriculum changes. Thus, this article also serves as a reference for schools and policymakers in enhancing the function and role of libraries in an increasingly complex educational landscape. Abstrak Artikel ini bertujuan untuk mengkaji peran strategis perpustakaan sekolah dalam mendukung implementasi Kurikulum Merdeka di tingkat Sekolah Menengah Pertama (SMP). Penelitian ini dilakukan melalui wawancara langsung dengan pengelola perpustakaan serta observasi terhadap perangkat dan fasilitas pendukung yang tersedia. Fokus utama dari kajian ini adalah bagaimana perpustakaan menyediakan bahan ajar yang efektif, relevan, dan menjalin koordinasi dengan guru dalam menunjang kegiatan belajar mengajar, serta melakukan berbagai inovasi untuk menyesuaikan diri dengan tuntutan Kurikulum Merdeka yang lebih fleksibel dan berpusat pada peserta didik. Perpustakaan tidak hanya berfungsi sebagai tempat membaca, tetapi juga sebagai pusat sumber belajar yang mendukung pengembangan literasi dan kemandirian belajar peserta didik. Hasil temuan dalam penelitian ini diharapkan dapat memberikan gambaran menyeluruh mengenai kontribusi perpustakaan sekolah dalam menciptakan lingkungan belajar yang adaptif dan responsif terhadap perubahan kurikulum. Dengan demikian, artikel ini juga menjadi rujukan bagi pihak sekolah dan pemangku kebijakan dalam meningkatkan fungsi dan peran perpustakaan di era pendidikan yang terus berkembang. Kata Kunci: Kurikulum Merdeka; pembelajaran; perpustakaan sekolah